Ideas, interests and foreign aid - Van der Veen, A. Maurits (Cambridge University Press CambridgeGB, 2011)
Examines the factors shaping foreign aid. Argues that the central factor overlooked in the literature on aid is ideational, i.e. ideas about the goals and purposes of aid policy which shape its formulation and implementation. Aims to show that it is possible to measure, rather than assume motivation, and that doing so can improve understanding of foreign policy decision-making.